1984
DOI: 10.1002/art.1780270607
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes in the skin of patients with progressive systemic sclerosis

Abstract: Mononuclear cells (MNC) present in the dermis of the forearm and in the blood of patients with progressive systemic sclerosis (PSS) were quantified and analyzed for subsets using monoclonal antibodies. The findings were correlated with cutaneous and systemic features of the disease. Total T lymphocytes and their subsets, B cells, and macrophages were enumerated in the skin samples of 21 patients with PSS. The dermal MNC infiltrates consisted mostly of activated T lymphocytes with a mean T helper/T suppressor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
201
1
7

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(218 citation statements)
references
References 24 publications
6
201
1
7
Order By: Relevance
“…It has The ligation of CD40 in vivo relies on the presence of CD154-expressing cells in the lesional skin of SSc patients. Pathological studies have shown the infiltration of T cells [15] and mast cells [22] in lesional skin at the earliest phase of the disease. Recently, it was reported that the expression of CD154 on activated T cells in peripheral circulating lymphocytes of SSc patients is significantly increased compared to that of normal donors [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has The ligation of CD40 in vivo relies on the presence of CD154-expressing cells in the lesional skin of SSc patients. Pathological studies have shown the infiltration of T cells [15] and mast cells [22] in lesional skin at the earliest phase of the disease. Recently, it was reported that the expression of CD154 on activated T cells in peripheral circulating lymphocytes of SSc patients is significantly increased compared to that of normal donors [23].…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of lesional skin biopsies from SSc patients, it has been reported that one of the earliest abnormalities is a collapse of vimentin intermediate filaments around the nucleus of endothelial cells [14]. Then both CD4-positive and CD8-positive T cells migrate into skin tissues [15]. Additional morphological and functional changes of fibroblasts and endothelial cells are noted coincident with the infiltration of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although the physiological roles of this cytokine remain largely unknown, OSM has been shown to exert a variety of effects on different types of cells. Studies have shown that fibroblasts are target cells for OSM (23,24,36,37) and that T-lymphocyte and monocyte/macrophage infiltration is observed in normal dermal repair as well as fibrotic lesions (38,39). Therefore, OSM could play a role in dermal fibrotic repair or fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of that study also showed a correlation between the reduced number of NKT cells and increased inflammation, suggesting that these cells play a regulatory role in SSc. The absolute and relative numbers of CD4ϩ T cells in SSc patients are normal, whereas those of CD8ϩ T cells are decreased (6). Since CD4ϩ T cells represent the predominant T cell infiltrate in the skin of SSc patients during the inflammatory phase of the disease and since there is a strong HLA class II major histocompatibility complex association with the autoantibody profile, clinical subsets (32,33), and T cell responses (34), most studies to date have been focused on CD4ϩ T cells.…”
mentioning
confidence: 94%
“…Several lines of evidence suggest that T cells are important in the pathogenesis of SSc, including observations that ␣/␤ and ␥/␦ T lymphocytes exhibit increased expression of activation markers (3,4), show signs of antigen-driven expansion (5), and dominate the inflammatory infiltrates in the skin and involved tissues during the early stages of the disease (6,7). T cells have been found to be necessary for the production of antitopoisomerase I antibodies in SSc (8).…”
mentioning
confidence: 99%